Предмет: Алгебра, автор: Аноним

помогите пожалуйста """"

Приложения:

Ответы

Автор ответа: dopecaliforniaoznjz5
1

\frac{m}{m^2-n^2} :\frac{n}{m^2-mn} =\\=\frac{m*m(m-n)}{(m-n)(m+n)n} =\\=\frac{m^2}{mn+n^2}

\frac{(a+b)^3}{(a^2-2ab+b^2)^3} :\frac{a^2+2ab+b^2}{(a-b)^5} =\\=\frac{(a+b)^3(a-b)^5}{(a+b)^6(a+b)^2} =\\=\frac{a+b}{a-b}

\frac{h^8-g^8}{gh^4-g^5} :\frac{h^4+g^4}{h^3-hg^2} =\\=\frac{(h^2-g^2)(h^2+g^2)(h^4+g^4)(h^3-g^2h)}{g(h^2-g^2)(h^2+g^2)(h^4+g^4)}=\\=\frac{h^3-g^2h}{g}

Похожие вопросы
Предмет: Обществознание, автор: tima222221